Gametogenesis in Malaria Parasites Is Mediated by the cGMP-Dependent Protein Kinase - McRobert, Louisa; Taylor, Cathy J; Deng, Wensheng; Fivelman, Quinton L; Cummings, Ross M; Polley, Spencer D; Billker, Oliver; Baker, David A (PLOS Biology, 2008)
We show that differentiation of malaria parasites in response to environmental signals encountered upon entering the mosquito following a blood meal is mediated by the parasite cGMP-dependent protein kinase.